How does overweight affect bone mineral density and oral health in adult hypophosphatasia?– A single center experience - Florian Dudde; Dominik Fildebrandt; Karin Petz; Ralf Smeets; Martin Gosau; Michael Amling; Thomas Beikler; Florian Barvencik (Orphanet Journal of Rare Diseases)
Abstract Aim The aim of this study was to investigate the influence of overweight (BMI ≥ 25 (kg/m²)) on the oral health status in patients with adult hypophosphatasia (HPP). Materials and methods Throughout a retrospective assessment both oral health status and bone metabolism including dual x-ray absorptiometry (DXA) for bone mineral density (BMD) measures were analyzed. The oral health status was assessed by the decayed/missing/filled teeth index (DMFT), clinical attachment level (CAL), probing pocket depth (PPD), and the periodontal screening index (PSI). The study population was divided into two groups based on the overweight classification by BMI (Overweight = BMI ≥ 25 kg/m²; n = 17) vs. non-overweight ( BMI < 25 kg/m²; n = 31). Results 48 HPP patients were included in this study. Overweight HPP patients showed a significantly reduced oral health status regarding filled teeth, DMFT, PSI, PPD and periodontitis severity index compared to non-overweight HPP patients. Furthermore, overweight HPP patients revealed significantly higher DXA findings regarding BMD, T- and Z-scores. Conclusion In the present study overweight (BMI ≥ 25 (kg/m²)) is associated with a poorer oral health status and higher BMD in adult HPP. Clinical relevance Since overweight is associated with a poorer oral health status in the general population and promotes the development of periodontal disease, the findings of the present study indicate that overweight also affects oral health in adult HPP.